MULTIDRUG-RESISTANT ACINETOBACTER BAUMANNII FROM NOSOCOMIAL URINARY TRACT INFECTION: A CASE REPORT - Srirangaraj, Sreenivasan; Segar, Lavanya; Kali, Arunava (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  The worldwide emergence of multidrug-resistant (MDR) Acinetobacter baumannii and high morbidity and mortality associated with this infection, present a challenge to clinicians. Emergence of resistance to multiple classes of antibiotics has limited the therapeutic options. In this case report, we describe the clinical presentation, risk factors, laboratory evaluation and therapeutic outcome of a 70-year-old patient who developed nosocomial urinary tract infection caused by MDR A. baumannii due to prolonged stay in intensive care unit, exposure to broad spectrum antibiotics and indwelling urinary catheter. Keywords: Acinetobacter baumannii, Urinary tract infection, Nosocomial infection, Antimicrobial resistance.